Western modernity encounters Asian tradition: national identity and nationalism in Iran - Alam, Homayun (Penerbit Universiti Kebangsaan Malaysia, 2020)
Iran and Iranians experienced an Islamic political upheaval after the Revolution of 1979, which led to national, ethnical, and religious modifications. After that process, the open-end question was raised in which course the Iranian nation will move on: western multiple modernity vs. Iranian tradition? The Iranian nation, which has a heterogeneous composition, does not differ significantly from its neighboring nations and the region around Western, Southern and Central Asia: We only think of the same languages, religions, and everyday social cultures that one can detect in Iran and its surrounding area. Territorially embedded in West Asia, but bordering Central and South Asia, Iran is bounded and equally populated by Turkish, Russian, Arab, Pakistani, Persian-Afghan and other nations. Only in a balanced - i.e. democratic, civic and inclusive relationship - Iran can assert itself in the long-term economically, culturally and religiously with its many ethnicities, languages and religions, and neighbors. This article seeks the question what and how the Iranian nation displayed superiority, say nationalism: Especially, the case of representation, (re-)construction of identity through different politicians active in cultural affairs or just diplomats are matters of fact in this article. The work and reflections of politicians and diplomats were to this point parameters of inclusion and exclusion to and in the Iranian nation. Finally, the following text centers on the last 20th and the current 21st century.